2009
DOI: 10.1007/s00436-009-1696-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity of internal transcribed spacer-1 (ITS-1) region of Eimeria infecting chicken and its relevance in species identification from Indian field samples

Abstract: Conventional method of species identification in Eimeria employs phenotypic characters of the oocysts and the site of infection in the chicken intestine, which are subjective analyses. PCR-based identification of Eimeria spp. is known to be specific and sensitive. We used internal transcribed spacer 1 (ITS-1)-based nested PCR to follow the distribution of Eimeria spp. in the field, which may be of significant value in the management of coccidiosis in chickens. In the present study, intestinal samples of chicks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…The present findings are in agreement with the findings of Bhaskaran et al (2009). However involvement of E. tenella in many outbreaks has also been documented from other parts of India (Jithendran 2001;Aarthi et al 2010;Jadhav et al 2011).…”
Section: Discussionsupporting
confidence: 83%
“…The present findings are in agreement with the findings of Bhaskaran et al (2009). However involvement of E. tenella in many outbreaks has also been documented from other parts of India (Jithendran 2001;Aarthi et al 2010;Jadhav et al 2011).…”
Section: Discussionsupporting
confidence: 83%
“…1 and Supplementary Table 2). These gaps may have been due to variations in the ITS-1 sequence, as has been reported previously in the case of E. tenella from India (Bhaskaran et al, 2010). While it is clear that PCR can facilitate the detection of minority Eimeria species sub-populations which may be missed by routine microscopy (Frölich et al, 2013), the reliance of PCR on very small primer annealing sites within a target genome also risks false negatives where genetic diversity occurs.…”
Section: Discussionmentioning
confidence: 59%
“…Of the 18 samples, 16 were also found to contain medium sized oocysts (NTP group) while 14 samples were found to contain the large sized oocysts (BM group). Previous studies carried out in Czechoslovakia (Kucera 1990), France (Williams et al 1996) and Korea (Lee et al 2010) reported E. acervulina to be the most highly prevalent species, while studies in China (Sun et al 2009), India (Bhaskaran et al 2010), Jordan (Al-Natour et al 2002 and Iran (Hadipour et al 2013) showed E. tenella to be highly prevalent. These studies conducted in countries from several regions of the world show that both E. acervulina and E. tenella are common among chicken farms, which is consistent with the occurrence of AM and NTP Eimeria species found in the 18 samples.…”
Section: Resultsmentioning
confidence: 94%